Pengaruh Pemberian Motivasi Belajar Guru Terhadap Hasil Belajar Matematika pada Materi Pengelompokkan Bangun Datar di Kelas II SDN Kwadungan LOR - Agustiani, Trismelinda Ayu; Nur'afifah, Uci Ulfa; Anfa, Qurrotul (Global Education Journal, 2023)
This research aims to determine the teacher's learning motivation towards students' mathematics learning outcomes in the material of grouping flat shapes in class II at SDN Kwadungan Lor. The type of research used is quantitative, with a one group pretest-posttest design method. The subjects in this research were class II students at Kwadungan Lor Elementary School with a total of 13 students. This research instrument uses questionnaires and tests. Based on data that has been collected and analyzed by SPSS 25 software, the variable studied is the provision of forms of teacher learning motivation for the material on grouping flat shapes. Based on the research results, it shows that providing teacher learning motivation has a significant influence as seen from the significance results (2-tailed) 0.00 < 0.05 with t count -12.619 < 2.365. This is supported by data from the results of the questionnaire as much as 53.8% in the high category, which means that students have been motivated by the gifts given by the teacher through the material on grouping flat shapes.